New Multiple Access Technologies for Satellite Internet of Things System - Wei BAI; Yujie ZHANG; Shaoli KANG; Deshan MIAO; Shaohui SUN; Shanzhi CHEN (天地一体化信息网络)
For satellite internet of things (IoT) scenarios with high propagation delay and the need to serve a larger number of users, firstly the shortcomings of IoT NTN in terms of technical solutions were analyzed, and then a new type of multi access solution called uncoordinated random access and NOMA transmission (URAT) was proposed.“Uncoordinated” refers to the process where a terminal does not require specialized network coordination signaling; “NOMA transmission” refers to the sharing of base station time-frequency resources by all terminals; URAT also achieves the integration of multiple access and NOMA transmission.Theoretical analysis and numerical simulation results indicated that the proposed scheme could reduce multi access latency, improve system efficiency, and increase the number of devices that could be served.It will be a potential solution for the 6G satellite IoT scenarios.